School of journalism: a warranty to strenghten the journalist profession and the development of a citizenship culture - Portugal de Rodrich, Maria Luisa (2006)
The idea is to form berter journalists, in order to make them collaborate in preparing better citizens, able to build more developed and fair societies. In this work we want to promote proposals leading to revalue the role of the Peruvian journalist. An urgent and vitally committing task, since the warranty of freedom of expression as well as the citizen's rights to receive opportune information depends on this measure.